Mapping principal navigations in the Levant - Stevenson, E (Taylor and Francis, 2022)
Richard Hakluyt’s The Principal Navigations, voyages, traffiques and discoveries of the English nation is a seminal work in the historical narrative of English exploration and colonisation. Its two editions, published in 1589 and 1598-1600 respectively, are behemoth volumes composed of texts from multiple sources. The narrative of English expansion and mercantile strength they depict has been fundamental within nationalist historiography, but both the sources and their editorial treatment were the result of Hakluyt’s personal involvement in socio-political networks, creating a bias in the text which has historically been overlooked. The material Hakluyt collected documenting English activities in the eastern Mediterranean and Levant region is a particularly useful case study of his editorial practices. By comparing a network map of the contemporary Anglo-Levant community with textual analysis of Principal Navigations, this article will demonstrate the ways in which these practices reinforced Hakluyt’s personal biases in the text’s portrayal of the Levant and eastern Mediterranean, how this bias has resonated in the following centuries to colour conceptions of the late sixteenth century English-Levant relationship, and suggest avenues for the study of unexplored perspectives on this history.